How ethnic diversity affects economic Development? - Erkan Gören (University of Oldenburg, Department of Economics, 2012)
This paper investigates the empirical relationship between the two concepts of ethnicity and economic growth. Ethnicity is assumed to affect economic growth through a number of possible transmission channels that are generally included in cross-country growth regressions by proposing an extended econometric system of equations to describe growth incorporates new channel variables for the potential indirect effects of ethnicity that are important in the process of economic development. The results, based on a sample of 95 countries for the period 1960-1999, suggest that the concept of ethnic fractionalization is a strong predictive measure for the direct effect of ethnicity on growth, whereas the concept of ethnic polarization has non-negligible indirect economic effects through the specified channel variables.
Keywords: O11; O5; 330; ethnic diversity; fractionalization; polarization; transmission channels; economic growth; Wirtschaftswachstum; Ethnische Beziehungen; Schätzung; Welt